2016
DOI: 10.18632/oncotarget.7167
|View full text |Cite
|
Sign up to set email alerts
|

HIF2α contributes to antiestrogen resistance via positive bilateral crosstalk with EGFR in breast cancer cells

Abstract: The majority of breast cancers express estrogen receptor α (ERα), and most patients with ERα-positive breast cancer benefit from antiestrogen therapy. The ERα-modulator tamoxifen and ERα-downregulator fulvestrant are commonly employed antiestrogens. Antiestrogen resistance remains a clinical challenge, with few effective treatments available for patients with antiestrogen-resistant breast cancer. Hypoxia, which is intrinsic to most tumors, promotes aggressive disease, with the hypoxia-inducible transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…We acknowledge our in vitro data may have limitations as this was generated from a single cell line, MCF-7 and its isogenic tamoxifen-resistant variant developed in house over 21 months [29, 30]. Nevertheless this is consistent with other work in this field where MCF- 7 is widely regarded as the most suitable cell line to study tamoxifen resistance due to its expression of ERα and exquisite hormone sensitivity in vitro [31], with recent publications using single MCF-7 derivatives [32, 33]. …”
Section: Discussionsupporting
confidence: 67%
“…We acknowledge our in vitro data may have limitations as this was generated from a single cell line, MCF-7 and its isogenic tamoxifen-resistant variant developed in house over 21 months [29, 30]. Nevertheless this is consistent with other work in this field where MCF- 7 is widely regarded as the most suitable cell line to study tamoxifen resistance due to its expression of ERα and exquisite hormone sensitivity in vitro [31], with recent publications using single MCF-7 derivatives [32, 33]. …”
Section: Discussionsupporting
confidence: 67%
“…5 J and K). The fact that HIF-2α expression also occurred in ∼26% of ER − tumors with absent or low FOXA1 suggests additional regulatory mechanisms of HIF-2α activation, possibly via high GFR-related signaling (40), as also shown in neuroblastoma (41).…”
Section: Activation Of Se Formation Is Correlated With Reprogrammed Fmentioning
confidence: 71%
“…However, we show that HIF-2α up-regulation is concordant with H-FOXA1 across our multiple endocrine-resistant cell models grown under nonhypoxic conditions. Noticeably, high GFR-related signaling, such as EGFR, has been shown to induce HIF-2α expression in endocrine-resistant BC cells (40). Therefore, both H-FOXA1-induced SEs and high GFR-related signaling (10), which also activates FOXA1, may converge to activate HIF-2α transcription and signaling in endocrine-resistant BC.…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate that HIF-2α can enhance the stemness phenotype of breast cancer cells to induce resistance to PTX. Alam et al reported that HIF-2α contributed to antiestrogen resistance via positive bilateral crosstalk with EGFR in breast cancer cells [ 32 ]. However, mechanisms in the resistance of breast cancer cells to PTX induced by HIF-2α remain unclear.…”
Section: Discussionmentioning
confidence: 99%